MOTIVASI KEWIRAUSAHAAN PETANI PADI ORGANIK DI KABUPATEN BANTUL - Nur Ratmawati; Triyono Triyono; Sriyadi Sriyadi (Universitas Sebelas Maret, 2015)
The improvement of farmers’ welfare, especially rice farmers require efforts to improve the ability of farmers to produce quality products and which is competitive. An effort that can be done is to increase the motivation of entrepreneur communities through organic farming which can be expected to ensure the preservation of the environment for sustainable production, achieve food security at the same time improving the welfare of people that having quality.This research aims to identify the motivation of entrepreneur farmers and the individual factors and the influence of environments. The study was conducted by interview survey method on organic rice farmers, then it was analyzed by descriptive and regression analysis. The results showed that the general motivation of entrepreneur farmers is strong enough. Factors that influence entrepreneurmotivation is the business environment; access to credit, market orientation, a network of cooperation and support from the government as well as individual factors, namely education.